Climate-smart agriculture application at the Near East and North Africa region focusing on Egypt - Abdel-Monem, Mohamed (2019)
As part of the IFPRI Egypt Seminar in partnership with the American University in Cairo: “Climate-Smart Agriculture Solutions for Egypt”